Co-production of extended-spectrum beta-lactamases and metallo beta-lactamases among multi-drug resistant gram-negative bacteria isolates collected from tertiary hospitals in Oyo State, Nigeria (2020)
Extended-spectrum beta-lactamases (ESBLs) and metallo beta-lactamases (MBLs) are compromising the chemotherapeutic use of cephalosporins and carbapenems respectively. This study investigated the burden of ESBLs and MBLs co-production among multi-drug resistant (MDR) Gram-negative bacteria collected from two tertiary hospitals in Oyo State. A total of 240 non-duplicated clinical isolates of Escherichia coli, Klebsiella spp. and Pseudomonas spp. were collected from the Microbiology units of two tertiary hospitals in Oyo State and their identities authenticated using standard identification techniques. Antimicrobial susceptibility testing was carried out by disc-diffusion method and isolates exhibiting resistance to 3 classes of antibiotics selected as MDR strains. ESBL and MBL production was detected by double-disc synergy test (DDST) and combined-disc-diffusion test (CDDT) respectively. Selected beta-lactamase genes were detected by PCR, amplicons sent out for sequencing and phylogenetic tree of the sequences constructed using Mega X software. MDR was exhibited by 43.8% of the isolates. ESBLs and MBLs were produced by 32.4% and 7.6% of the MDR isolates respectively. Co-production of ESBL and MBL was observed in 6.7% of the MDR isolates. BlaCTX-M-15 (67.7%), blaTEM-1 (55.9%), blaSHV-1 (47.1%), co-existing blaTEM + blaSHV, blaTEM + blaCTXM, blaCTX-M + blaSHV (each in 5.9%) and blaCTX-M +blaTEM + blaSHV (26.5%) were detected among the ESBLproducers. MBL genes were not detected among the MBL-producers. Only blaTEM-1 sequences showed two different claudes on the phylogenetic tree. The occurrence of MDR isolates co-harbouring different classes of beta-lactamse genes observed in this study is of public health concern and hence, requires stricter control of antibiotic use.